2019
DOI: 10.3389/fmicb.2019.02552
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Culture Filtrate Enhances the Growth of Gemmata spp.

Abstract: BackgroundPlanctomycetes bacteria are known to be difficult to isolate, we hypothesized this may be due to missing iron compounds known to be important for other bacteria. We tested the growth-enhancement effect of complementing two standard media with Escherichia coli culture filtrate on two cultured strains of Gemmata spp. Also, the acquisition of iron by Gemmata spp. was evaluated by measuring various molecules involved in iron metabolism.Materials and MethodsGemmata obscuriglobus and Gemmata massiliana wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Testing co-culture of Gemmata spp. with E. coli filtrate, we showed that the number of both G. obscuriglobus and Gemmata massiliana colonies were significantly higher on basic medium supplemented with E. coli filtrate than on the standard medium (p < 0.0001) (Kaboréet al, 2019a). Hence, cooperating groups might exist between uncultured Planctomycetes and Proteobacteria like E. coli for siderophore and iron acquisition, which causes the interests of these individuals to be associated with those of the group and other such as Verrucomicrobia and Actinobacteria (D'Onofrio et al, 2010).…”
Section: Planctomycetes Associated With Other Bacterial Communitiesmentioning
confidence: 90%
“…Testing co-culture of Gemmata spp. with E. coli filtrate, we showed that the number of both G. obscuriglobus and Gemmata massiliana colonies were significantly higher on basic medium supplemented with E. coli filtrate than on the standard medium (p < 0.0001) (Kaboréet al, 2019a). Hence, cooperating groups might exist between uncultured Planctomycetes and Proteobacteria like E. coli for siderophore and iron acquisition, which causes the interests of these individuals to be associated with those of the group and other such as Verrucomicrobia and Actinobacteria (D'Onofrio et al, 2010).…”
Section: Planctomycetes Associated With Other Bacterial Communitiesmentioning
confidence: 90%
“…LF2 revealed that Cu is more toxic than Zn at the same concentration [59], which also appeared to be the case for P. limnophila based on our OD 600 measurements in the liquid phase. However, the MTT assay for Cu (50) and the crystal violet staining for Cu (50) and Cu (100) generated higher absorbance values compared to Zn, indicating a stronger positive effect on sessile growth. The stabilizing effect of cationic metal ions, such as Cu, Zn, and Fe, on B. subtilis biofilms has been previously demonstrated [55].…”
Section: Discussionmentioning
confidence: 93%
“…In earlier studies, the growth of Gemmata spp. was enhanced by the addition of FeSO 4 [50] and two planctomycetal strains isolated from Fe(OH) 2 deposits were found to be attached to Fe precipitates [51]. Fe promotes biofilm formation in Pseudomonas aeruginosa [52,53], Escherichia coli [54], Bacillus subtilis [55], Staphylococcus aureus [56], and Vibrio cholerae [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations